2023
DOI: 10.1021/acssuschemeng.2c07658
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Strain Engineering of Copper Atoms on Continuous Three-Dimensional-Nanopatterned Nickel Nitride to Accelerate Alkaline Hydrogen Evolution

Abstract: Maximizing electrocatalytic activity by incorporating heteroatoms into the microstructures of non-noble metal catalysts is vital for their application in industrial water-alkali electrolyzers, yet modulation of the catalytic properties by the synergistic effects of three-dimensional (3D) nanopatterning and the incorporation of heteroatoms remains challenging. Here, we fabricated a tunable Cu atom-incorporated continuous 3D-nanopatterned nickel nitride (Ni 3 N) and investigated its electrocatalytic activity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Currently, while platinum-based catalysts find extensive application in the water electrolysis producing hydrogen industry, the scarcity and elevated cost of the precious metal platinum pose significant constraints on its continued advancement. Additionally, in an alkaline environment, the constrained water molecule adsorption and dissociation capabilities of precious metal platinum impede the optimal performance of platinum–carbon catalysts. Consequently, the pursuit of a nonplatinum alkaline electrocatalytic hydrogen evolution reaction (HER) catalyst emerges as a pivotal driver for the progression of the electrolytic water hydrogen production industry. The cost-effective precious metal ruthenium (Ru) has garnered substantial attention among researchers due to its economic viability (costing less than half of the precious metal platinum) and its robust adsorption and dissociation affinity for water molecules. Nevertheless, challenges persist in the development of a high-performance Ru-based catalyst and in unraveling its structure–activity relationship under realistic reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, while platinum-based catalysts find extensive application in the water electrolysis producing hydrogen industry, the scarcity and elevated cost of the precious metal platinum pose significant constraints on its continued advancement. Additionally, in an alkaline environment, the constrained water molecule adsorption and dissociation capabilities of precious metal platinum impede the optimal performance of platinum–carbon catalysts. Consequently, the pursuit of a nonplatinum alkaline electrocatalytic hydrogen evolution reaction (HER) catalyst emerges as a pivotal driver for the progression of the electrolytic water hydrogen production industry. The cost-effective precious metal ruthenium (Ru) has garnered substantial attention among researchers due to its economic viability (costing less than half of the precious metal platinum) and its robust adsorption and dissociation affinity for water molecules. Nevertheless, challenges persist in the development of a high-performance Ru-based catalyst and in unraveling its structure–activity relationship under realistic reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal chalcogenides (TMCs) have gained significant attention as efficient catalysts due to their decent activity, particularly among the various non-noble metal catalysts. Recently, there has been considerable interest in exploring Ni- or Co-based metal sulfides as potential catalysts for the acidic HER, primarily because of their engineering versatility and cost-effectiveness. Earlier research has indicated that the electrochemical activity of CoSe 2 and NiSe 2 is attributed to the presence of chalcogenide atoms at their edges, similar to what has been observed in MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite precious catalysts like RuO 2 and IrO 2 being considered the most efficient commercial OER catalysts, their widespread use is limited by low abundance, high prices, and poor stabilities. Therefore, construction of high-performance non-precious metal-based OER catalysts is essential to facilitate the commercial application of clean energy conversion devices. …”
Section: Introductionmentioning
confidence: 99%